2011
DOI: 10.1600/036364411x605100
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny and Biogeography of Ivies (Hedera spp., Araliaceae), a Polyploid Complex of Woody Vines

Abstract: Ivy (Hederá spp., Araliaceae) is a polyploid complex of woody vines. Native to Eurasia and northern Africa, ivy is cultivated worldwide and has become an aggressive invader of North American forests. Despite its ecological impacts and economic significance to the horticultural industry, the taxonomy of Hederá is controversial and historical relationships are poorly defined. Here we characterize the phylogeny of Hederá based on the low-copy nuclear locus Granule-bound starch synthase I (GBSSI) and twelve non-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
39
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 48 publications
(58 reference statements)
4
39
0
4
Order By: Relevance
“…Carrière describing these ivies fell into oblivion, largely because most of them have always been considered, as he supposed, varieties and forms of H. helix. Nevertheless, in recent years his work has been claimed to name the ivy from Azores Islands, as most authors (McAllister & Rutherford, 1997;López González, 2001;Schäfer, 2002Schäfer, , 2003Valcárcel & al., 2003;Green & al., 2011;Schäfer & al., 2011) consider it as a new species: H. azorica Carrière, Rev. Hort.…”
Section: Hedera Cordatamentioning
confidence: 99%
See 1 more Smart Citation
“…Carrière describing these ivies fell into oblivion, largely because most of them have always been considered, as he supposed, varieties and forms of H. helix. Nevertheless, in recent years his work has been claimed to name the ivy from Azores Islands, as most authors (McAllister & Rutherford, 1997;López González, 2001;Schäfer, 2002Schäfer, , 2003Valcárcel & al., 2003;Green & al., 2011;Schäfer & al., 2011) consider it as a new species: H. azorica Carrière, Rev. Hort.…”
Section: Hedera Cordatamentioning
confidence: 99%
“…Some of these names have recently been used as names of accepted species in the genus Hedera L. (Araliaceae). Such is the case of Hedera azorica Carrière, a name that many authors (McAllister & Rutherford, 1997;López González, 2001;Schäfer, 2002Schäfer, , 2003Valcárcel & al., 2003;Green & al., 2011;Schäfer & al., 2011) used for the plant growing on the Atlantic islands indicated by its specific epithet, and indeed attributed the name to E.A. Carrière ("Elie Abel Carrière 1818-1896.…”
mentioning
confidence: 99%
“…Geographical groups of taxa can include diff erent ploidy levels, diploids, and polyploids. Th ese studies also revealed that formerly used morphological traits such as trichome morphology are not considered evolutionarily stable in ivies (Green et al 2011, Vargas et al 1999.…”
Section: Introductionmentioning
confidence: 98%
“…In the last decades several morphological (Ackerfield and Wen 2002, Kost et al 2003, Sulgrove 2004, Valcárcel and Vargas 2010) and molecular studies (Vargas et al 1999, Grivet and Petit 2002, Green et al 2011 were performed on Hedera taxa with the aim of revealing phylogenetic relationships and evolution. However, molecular studies followed by cytometric measurements revealed that polyploidy was the major phenomena in the evolution of Hedera species, and might have taken place several times independently in diff erent lineages (Green et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation